Measuring Inflow of Remittances in Six ASEAN Countries Using Macroeconomic Variables: Panel Data Analysis - Jintan, Andam Rani; Nahar, Faiza Husnayeni; Azizurrohman, Muhammad (Journal of Economics Research and Social Sciences, 2020)
Tempted by the economic potential offered by other countries makes people flocked to get the opportunity to improve their economy. Evidenced by the large number of international migrants throughout the world, this figure is in line with the high total remittance flow that leads to their country of origin. Countries in ASEAN become remittance recipients with quite high growth each year, so it is interesting to study further. Using panel data from six countries in ASEAN in 2000-2016, per capita Gross Domestic Product (GDP), domestic inflation, exchange rates, age dependency ratios and financial development are included as variables that affect remittances. The analytical method used is panel data with Fixed Effect Model (FEM). The results of the panel data found that the independent variables, including GDP per capita, domestic inflation, exchange rates, age dependency ratios and financial developments had a positive and significant effect on remittance flows in ASEAN in the period of 2000-2016